The Advanced Placement Program is Missing Something: Underrepresentation of Latinx Students in AP Classes. (International Social Science Review, 2025)
The article focuses on the underrepresentation of Latinx students in Advanced Placement (AP) classes and the systemic barriers contributing to this issue. Despite the AP program's growth since its inception in 1952, access and success rates for Latinx students remain disproportionately low compared to their White and Asian peers, largely due to socioeconomic factors, resource disparities in schools, and geographical limitations. The article discusses various barriers, including costs associated with AP classes and exams, lack of information and support for families, and insufficient culturally relevant course offerings. It suggests strategies for improving access, such as expanding course offerings, enhancing teacher training, and increasing outreach to families, while emphasizing the need for greater investment in educational equity to support Latinx students in AP programs.